An analysis of slabs-on-grade as an anchorage system for tilt-up concrete panel temporary braces - Engelland, Dillon John (Kansas State University, 2021)
An analysis of concrete slabs-on-grade as a means of anchorage for temporary bracing of tilt-up concrete panels is presented within this report. A tilt-up concrete panel of 42 feet in height, 26 feet in width, and 9.25 inches in thickness is a constant within the analysis, as is a construction period wind speed of 80 mph. The thickness of the concrete slab-on-grade and the subgrade material directly below the slab-on-grade are varied to achieve comparable results. ASCE 7-16’s procedure for determining wind load outlined in chapter 29 and ASCE 37’s provisions for construction period reductions in wind load are used to calculate the wind load on the face of the tilt-up panel. This wind load is then translated into a force taken directly by the temporary braces. This force transmitted through each brace is then divided into a vertical component and a horizontal component upon anchorage to the slab-on-grade for analysis. Two wind conditions are analyzed in the study, and each condition produces two different potential failure mechanisms that must be studied. The first wind condition is wind blowing on the exterior face of the panel. This wind condition causes the temporary braces to be in compression. With the braces in the compression, the slab-on-grade can fail horizontally as a result of slab sliding and vertically due to punching shear failure. The second wind condition is wind blowing on the interior face of the panel. This wind condition causes the temporary braces to be in tension. When the braces are in tension, pullout of the slab-on-grade anchor can occur, and the slab-on-grade can be lifted up due to the overturning moment of the wind load on the panel face. The different subgrade materials analyzed in this report are gravel, sand, soil, and a vapor retarder/barrier. The slab-on-grade thicknesses examined are 5-inch, 6-inch, and 8-inch. Each subgrade material has a different coefficient of friction and will affect the slab-on-grade’s resistance to sliding. The thickness of the slab-on-grade will affect the slab’s resistance to sliding, punching shear, and overturning moment. This report outlines how each variable is adjusted to determine the slab-on-grade’s adequacy as a means of anchorage for the temporary panel bracing. Results of the study show that all thicknesses of the slab-on-grade and subgrade conditions analyzed are adequate based on the assumed surface areas considered effective to resist against slab sliding and overturning. It is recommended that physical testing be conducted to determine exactly how the slab-on-grade acts at saw joint and control joint locations. The study assumes that control joint locations are boundary limits of slab surface area effective to resist against slab sliding, and it is also assumed that saw joint locations will not be subject to slab overturning failure due to the steel reinforcing continuous across the saw joint location. Both of these assumptions need to be studied and verified with physical testing.
Keywords: Tilt-up concrete panels; Temporary bracing; Slab-on-grade; Bracing connections